2017
DOI: 10.1252/jcej.16we023
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Bubble Behaviors for Gas–Liquid Dispersion in Agitated Vessel

Abstract: The present study mainly investigates bubble behaviors in an agitated vessel. Computational uid dynamics provides a method for exploring the complex uid ow in an agitated vessel. A stirred tank model with transport equation for the interfacial area concentration and force equilibrium equation for bubbles under multi-forces is created for a 43-dm 3 agitated vessel. The model considers the breakage and coalescence mechanism of the bubbles. The local gas holdup is measured by ber-optical probe. After this, the bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The bubble size in TPCFBs was not uniform in radial direction. It was reported that the bubble size in the riser of the TPCFB generally decreased with increasing the radial distance from the center, due to the tendency of bubbles to move to the center avoiding contact with the wall of the riser (Wang et al, 2001b;Kang et al, 2003;Liu et al, 2017). The effects of U G on the bubble size could depend on the experimental conditions and systems.…”
Section: Bubble Properties In the Risermentioning
confidence: 97%
“…The bubble size in TPCFBs was not uniform in radial direction. It was reported that the bubble size in the riser of the TPCFB generally decreased with increasing the radial distance from the center, due to the tendency of bubbles to move to the center avoiding contact with the wall of the riser (Wang et al, 2001b;Kang et al, 2003;Liu et al, 2017). The effects of U G on the bubble size could depend on the experimental conditions and systems.…”
Section: Bubble Properties In the Risermentioning
confidence: 97%